PENDAMPINGAN AKHLAK ANAK USIA DINI TERHADAP PEMBENTUKAN KARAKTER - Titik Zuliyanti; Nailatul Muna (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This community service (PkM) activity aims to strengthen early childhood character formation through Moral Guidance (Akhlak Pendampingan) at TPQ Al-Amin, Gombong Hamlet. The core urgency of the activity was the existing gap between religious theory and the practical application of moral conduct among students, coupled with the lack of a structured curriculum focused on character development within the TPQ. The methodology employed was the Asset-Based Community-Driven Development (ABCD) approach, leveraging the community assets, specifically the TPQ facility and full community support. Program implementation involved curriculum reformation through deliberation (Design), followed by the execution of three core activities (Destiny): Alala Book studies using the bandongan method, direct prayer practice, and ancestral tomb pilgrimage (ziarah kubur); all oriented towards practical moral behavior. The results demonstrated that the program successfully produced a sustainable new curriculum and significantly increased student enthusiasm and positive behavior (Akhlak). This success affirms that cultivating character education from an early age through interactive and community-based participatory methods is highly effective in shaping the character of the nation's children.